1989
DOI: 10.1161/01.hyp.13.6.612
|View full text |Cite
|
Sign up to set email alerts
|

Salt-induced hypertension in Dahl salt-sensitive rats. Hemodynamics and renal responses.

Abstract: This study was performed with Dahi salt-sensitive (DS) and Dahi salt-resistant (DR) rats to detect differences hi cardiovascular hemodynamics and renal responses that might be involved hi initiating salt-induced hypertension hi DS rats. The effects of 4 weeks of 8% NaCl diet were studied hi conscious, male DR and DS rats hi which vascular and urinary catheters had been previously implanted. Results were compared with those obtained from control groups of DR and DS rats on 4 weeks of 1% NaCl diet. DR rats on 8%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 28 publications
4
41
0
Order By: Relevance
“…At 4 and 8 weeks, DR rats on 8% NaCl had no statistically significant changes in TPR, CO, and BV. The 8% salt diet resulted in a significant expansion of BV (p <0.05) at 4 weeks (as previously reported 18 ) and 8 weeks in DS rats. At 4 weeks, DS rats on 8% NaCl had a marked increase in CO (p<0.05), whereas TPR was not significantly changed.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…At 4 and 8 weeks, DR rats on 8% NaCl had no statistically significant changes in TPR, CO, and BV. The 8% salt diet resulted in a significant expansion of BV (p <0.05) at 4 weeks (as previously reported 18 ) and 8 weeks in DS rats. At 4 weeks, DS rats on 8% NaCl had a marked increase in CO (p<0.05), whereas TPR was not significantly changed.…”
Section: Resultssupporting
confidence: 87%
“…16 ' 17 We previously reported that hypertension that developed in DS rats in response to a high salt diet (8% NaCI) for 4 weeks resulted, at least partly, from an inability of the kidney to vasodilate and to increase sodium and water excretion; an expanded blood volume (BV) and an increased cardiac output (CO) were responsible for the hypertension. 18 According to Guyton et al, 19 in the presence of an increased CO and augmented tissue blood flow, total peripheral resistance (TPR) increases significantly with "long-term autoregulation" (i.e., vasoconstrictor regulation of tissue perfusion), and CO returns to normal; elevated TPR then becomes responsible for the hypertension.…”
Section: % Nacimentioning
confidence: 99%
“…Increased renal vasculature resistance and reduced salt excretion have been determined in the Dahl salt-sensitive rat, and have been postulated to play a central role in the pathogenesis of hypertension (20,21). NO reduces renal vascular resistance, and increases sodium excretion (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…After a high NaCl diet, plasma and CSF volume expansion might obscure an increase in total sodium content if only sodium concentration is determined. We observed that after an 8% NaCl diet, hypertension in DS rats was initiated by blood volume expansion and increased CO but was perpetuated by increased TPR, 16 whereas prolonged ingestion of 1% NaCl caused hypertension by increasing TPR. 18 Conceivably, increased access of NaCl to the brain of DS rats may be responsible for the increased TPR.…”
Section: Discussionmentioning
confidence: 84%
“…An 8% NaCl diet causes rapid onset of severe hypertension initially because of blood volume expansion and elevated cardiac output (CO); however, CO rapidly returns to normal and hypertension is maintained by increased TPR, even though hypervolemia persists. 16,18 Our major objective was to determine how 22 NaCl is handled in prehypertensive DS and Dahl salt-resistant (DR) rats on a low NaCl (0.23%) diet before hemodynamic or structural abnormalities related to hypertension have occurred. Furthermore, we studied the effects of hypertension induced by 8% NaCl on the handling of 22 NaCl by the blood-brain barrier (BBB).…”
mentioning
confidence: 99%